Texture Analysis of Coated Conductors by Micro-Raman and Synchrotron x-ray Diffraction - Puig, Teresa; Molina, Anna Puig; Mestres, Narcis; van Seijen, Harm; Alzina, Francesc; Gonzalez, Juan Carlos; Obradors, Xavier; Graafsma, H.; Usoskin, Alexander; Freyhardt, H.C. (Mat. Res. Soc. Symp., 2001)
Two novel complementary and non-destructive techniques for texture analysis of YBCO coated conductors are presented. Micro-Raman (μ-Raman) spectroscopy enables an easy analysis of the film homogeneity by determining the distribution of a- and c-oriented grains within the tape with a 1 μm spatial resolution and acquisition times of 5 min/spot. In addition, synchrotron x-ray diffraction analysis in transmission geometry and 2D detectors enables, with acquisition times of 100 ms, simultaneous observation of a- and c- crystallites and in-plane textures of substrates, buffers and superconducting layer. Thus, opening the field of this technique to in-situ analysis of epitaxial growth of coated conductors prepared by ex-situ processes. Results from these two techniques for stainless steel tapes buffered with IBAD-YSZ and coated with PLD-YBCO are analyzed.